A PRAGMA-STYLISTIC ANALYSIS OF ISOKO APHORISMS - Maledo, Richard Oliseyenum; Ogboru, Lawrence Efe (International Review of Humanities Studies, 2023)
This paper is a study of Aphorisms in Isoko language. The Isoko language is one of the understudied minority languages facing threat of extinction from Nigerian Pidgin and the English language in the oil-rich Niger Delta region of Nigeria. Thus, in a bid to document and preserve aspects of the Isoko language, this paper undertakes a pragma-stylistic study of Isoko aphorisms. The data for the study consists of twelve (12) Isoko aphorisms collected from competent native speakers of Isoko through participant-observation method and recording and translated into English by a competent Isoko – English bilingual. They are then analysed using Lakoff and Johnson’s (1980 & 2003) Conceptual Metaphor theory as analytical tool to ascertain the conceptual mappings between the compositional meaning of an aphoristic expression (source domain) in Isoko and its actual pragma-stylistic content (target domain). The findings reveal that the correspondence between the source and target domains in Isoko aphorisms help in accounting for both pragma-stylistic and social meanings in the real world. It recommends that studies of this nature should be carried out in other areas as it has the potentials of not only preserving and developing the Isoko language but also increasing the phrasal stock of the emerging Nigerian English.